KOMUNIKASI DAKWAH BAGI PEMURNIAN AKIDAH UMMAT - M Amin Sihabuddin (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2018)
This paper describe purification method of proselytizing creed the ummah of the prophet (dakwah of faith). Based on the results of studies conducted by apostles preaching secretly in the first three years of prophethood, after it is done openly. Aqidah methods of prophet preaches, face to face, i’lam, (teaching), speech, literacy, correspondence, envoy, methods for purification of this aqidah is through worship only to Allah orders done via the law of Prayer, Charity, Fasting, Hajj. Especially with the people of the book is a dialogue about the principles of faith in Uluhiah dan Rububiah aspect. Aqidah propaganda material finally believe and trust purposes only Allah alone is the Creator and only Allah alone has the right to be worshiped. About the verses of the Quran relating to the Aqidah chapters, the companions never debated and asked the Prophet about the verse, but their trust and establish the nature of God, and they are not debating the nature and essence af’al.